How do savings and personal budgeting matter on financial literacy and well-being - Versal, Nataliia; Honchar, Ihor; Balytska, Mariia; Erastov, Vasyl (Business, Management and Economics Engineering, 2023)
Purpose – the well-being of individuals plays a vital role in fostering sustainable economic development. The differentiation between subjective and objective well-being in selected EU and selected non-EU countries, with a particular focus on financial literacy, as individuals’ assessments of their own well-being can significantly differ from objective economic indicators, emphasizing the subjective nature of well-being. The research objective is to investigate how savings and personal budgeting indicators affect both objective and subjective well-being and to examine the role of these indicators in promoting financial literacy.Research methodology – the research investigates the impact of savings and personal budgeting indicators on financial literacy (FLI), financial well-being (FWB), and gross domestic product at purchasing power parity per capita (GDP PPP per capita). We applied Pearson’s pairwise correlation between nine indicators of personal budgeting and savings and the method of principal components to identify the reasonable factors according to their statistical significance based on data from 22 countries included in the Organisation for Economic Cooperation and Development/International Network on Financial Education (OECD/INFE) survey data, Global Findex Database. The application of the Varimax procedure made it possible to identify factor groups of indicators.Findings – we identify two factors for the whole sample and a sample of selected EU-countries; for non-EU-countries were identified three factors. Our research reveals that subjective FWB across all countries and non-EU countries is under the significant influence of factor group 1 mainly represented by savings indicators, with no significance for EU countries. FLI also significantly depends on factor group 1 for the entire sample of countries and across EU and non-EU countries. GDP PPP per capita is under the significant influence of all factors both in the sample of countries and across EU and non-EU countries.Research limitations – FLI databases started to be gathered relatively recently and are not regularly updated. This can cause a situation when data for different countries are provided with time gaps. Moreover, due to the high cost involved, not all countries conduct such research, which hinders the creation of large datasets for more accurate country comparisons.Practical implications – the results of this study may have interest for policymakers since they focus on improvement of the financial literacy and FWB of individuals, that results in a higher level of financial stability.Originality/Value – this research is to address existing gaps in understanding of the interplay between subjective and objective FWB. Also, it proposes a novel approach that views savings as a factor that enhances financial literacy, in contrast to the conventional approach that considers savings as a consequence of improved FWB.